Model project-based learning berpendekatan budaya lokal Mandar: Studi eksperimen terhadap hasil belajar matematika siswa - Aslan Efendi; Aprisal Aprisal; Herna Herna (Mandalika Mathematics and Educations Journal, 2026)
This study aims to determine the effect of the project-based learning model with the Mandar local cultural approach on students' mathematics learning outcomes in class VIII of SMP Negeri 07 Campalagian, Polewali Mandar Regency, West Sulawesi. This study is a study with a One-Group Pretest-Posttest Design. The population in this study were all students of class VIII of SMP Negeri 07 Campalagian. The sampling technique used was the saturated sampling technique which is a sampling technique in which all members of the population can be used as samples. Research data were collected using a learning outcome test consisting of a Pretest and Posttest, as well as an observation sheet consisting of a sheet of learning implementation by the teacher and student activities. The results of data analysis show that students' mathematics learning outcomes after the application of project-based learning with the Mandar local cultural approach are in the high category with skor 80.21 so it can be concluded that there is an increase in the learning outcomes of students taught using the Project Based Learning model with the Mandar Local Cultural approach.